IMPROVING STUDENTS’ READING COMPREHENSION BY USING MAKE A MATCH TECHNIQUE AT THE EIGHT GRADE STUDENTS’ OF MTs AL FATTAH BANYUURIP UJUNGPANGKAH GRESIK - Abdullah Farih (Universitas Islam Lamongan, 2018)
Reading is a cognitive process of decoding symbols in order to construct or derive meaning (reading comprehension). The objective of this study is to know the application of Make a Match Techniqueto improve the students’ reading comprehension at the Eight grade students of MTs Al Fattah Banyuurip Ujungpangkah Gresik and to know whether Make a Match Technique is able to improve the students’ reading comprehension in descriptive text. The study was conducted at MTs Al Fattah Banyuurip Ujungpangkah Gresik. The subject of this study was 23 student. This study used Classroom Action Research (CAR) design. The research used pre-test, post-test and observation checklist.To know the students’ improvement in reading comprehension, the researcher uses instruments are test and observation checklist. From the result observation checklist it shows that teaching learning by using Make a Match technique can improve succesfully the students’ reading comprehension. The average of preliminary test is 56.82, the result of test cycle I is 73.21 and theb result of cycle II is 78.34.